2023
DOI: 10.1186/s13046-023-02786-y
|View full text |Cite
|
Sign up to set email alerts
|

Global serum profiling: an opportunity for earlier cancer detection

Abstract: The advances in cancer research achieved in the last 50 years have been remarkable and have provided a deeper knowledge of this disease in many of its conceptual and biochemical aspects. From viewing a tumor as a ‘simple’ aggregate of mutant cells and focusing on detecting key cell changes leading to the tumorigenesis, the understanding of cancer has broadened to consider it as a complex organ interacting with its close and far surroundings through tumor and non-tumor cells, metabolic mechanisms, and immune pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
0
0
Order By: Relevance
“…Early detection strategies can improve the e cacy of surgery and other interventional approaches while mitigating the economic and psychological burden associated with an advanced disease diagnosis. It is thus essential that easy-to-use, minimally invasive, cost-effective technologies be developed capable of detecting tumors when they are precancerous lesions or remain in the early stages of disease [29]. The present results revealed that CXCL8 expression was elevated in most surveyed tumor types as compared to corresponding normal tissues.…”
Section: Discussionmentioning
confidence: 54%
“…Early detection strategies can improve the e cacy of surgery and other interventional approaches while mitigating the economic and psychological burden associated with an advanced disease diagnosis. It is thus essential that easy-to-use, minimally invasive, cost-effective technologies be developed capable of detecting tumors when they are precancerous lesions or remain in the early stages of disease [29]. The present results revealed that CXCL8 expression was elevated in most surveyed tumor types as compared to corresponding normal tissues.…”
Section: Discussionmentioning
confidence: 54%